Genu valgum and arachnodactyly: a rare presentation in Wildervanck syndrome (Ukrainian Journal of Ophthalmology, 2025)
Background: Cervico-Oculo-acoustic syndrome, also known as Wildervanck syndrome, is a rare inherited disorder that causes congenital hearing loss, Klippel-Feil abnormalities, and Duane retraction syndrome. Females are more likely to have Wildervanck syndrome and associated skeletal and cranial anomalies. This illness's distinctive symptoms must be accurately documented to advance clinical knowledge and therapeutic strategies.Case Presentation: An eleven-year-old girl from a blood line had restricted neck movement and left eye abduction since birth. She had genu valgum, arachnodactyly, micrognathia, and other notable cranial anomalies.Interventions: Supportive treatment included neck mobility and scoliosis therapy, hearing aids for her conductive hearing loss, and genu valgum assessments. Genetic consultation assisted with family planning and inheritance patterns.Conclusion: As this example shows a rare phenotype, patients with Wildervanck syndrome may have more symptoms than previously considered. This patient’s limb malformations underscore the need for thorough clinical examination and genetic research. This paper provides a good starting point for comprehensive Wildervanck syndrome diagnosis, treatment, and genetic counseling.
Keywords: Genu valgum; arachnodactyly; Wildervanck syndrome; Klippel-Feil abnormalities; Duane retraction syndrome